PENGOLAHAN LIMBAH KULIT RAMBUTAN MENJADI PRODUK MINUMAN DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA RONG DURIN KABUPATEN BANGKALAN - Tri Wahyudi Ramdhan; M. Kholid (As-Sidanah, 2019)
Abstract: This Community Service stems from the desire to provide skills that can improve the economy in Rong Durin, Bangkalan by utilizing existing natural products so that they are more economically valuable. The benefit of rambutan natural resources is not the fruit only but the skin which has only become waste. Based on this phenomenon, the rambutan skin waste is extracted into a drink that is suitable for consumption. The method and approach used is problem solving with a short learning by doing method which is done through lectures, discussions and practices. While the results obtained from this activity are 1) the existence of knowledge and skills to process rambutan skin waste into rambutan tea drinks, 2) The product is produced in the form of rambutan tea from rambutan skin extraction. 3) Increased awareness of the environment and the creation of jobs. The two results above are expected to be able to improve the economy of the people of Rong Durin Village, the majority of whom are farmers